Aortoiliac arterial thrombosis and renal artery stenosis in a patient with neonatal multisystem inflammatory syndrome: a case report and review of literature - Lertkovit, Oranooj; Isaranimitkul, Daranee; Pornrattanarungsri, Suwanna; Sirimongkolchaiyakul, Ornatcha; Tangcheewinsirikul, Sirikarn; Saengrat, Pichada (Frontiers in Pediatrics, 2025)
BackgroundMultisystem inflammatory syndrome in neonates (MIS-N) is a rare condition thought to be associated with prenatal exposure to maternal severe acute respiratory syndrome coronavirus 2 infection. This immune-mediated hyperinflammation has been described in neonates with multiorgan dysfunction, including cardiopulmonary, encephalopathy, coagulopathy, and vascular complications. However, renovascular complications in MIS-N are rare. Here, we present a case with aortoiliac arterial thrombosis and renovascular stenosis in MIS-N.Case presentationA 2-day-old, full-term, male neonate presented with fever, respiratory failure, hypotensive shock, and elevated inflammatory markers. He was transferred to our neonatal intensive care unit for comprehensive monitoring and treated with antibiotics for early-onset neonatal sepsis. However, his clinical condition deteriorated. His mother reported a history of severe acute respiratory syndrome coronavirus 2 infection during the late second trimester. He was diagnosed with MIS-N based on the fulfillment of the diagnostic criteria for multiorgan involvement and laboratory findings. He responded to intravenous immunoglobulin, corticosteroids, and aspirin. However, he later developed significant hypertension, which was associated with aortoiliac arterial thrombosis and right renal artery stenosis. An elevated ferritin level was observed. The ongoing inflammatory condition was considered, and corticosteroids were restarted along with treatment for documented thrombosis using enoxaparin and aspirin. After treatment, partial resolution of aortoiliac arterial thrombus was observed. However, narrowing of the proximal part of right renal artery persisted, and blood pressure remained difficult to control, requiring multiple antihypertensive agents. Finally, the patient underwent percutaneous transluminal balloon angioplasty to control hypertension.ConclusionOur case revealed the clinical course of MIS-N with renovascular complications. The condition's hyperinflammatory state may have played a pathophysiological role in the development of this life-threatening complication. Although there is an increased risk of bleeding in MIS-N, thromboprophylaxis should be considered in high-risk patients. An early multidisciplinary approach is recommended to ensure prompt diagnosis and improve outcomes.